Tourism Therapy - Mehrnoosh Bastenegar (گردشگری فرهنگ, 2023)
In this text, we do not intend to focus on health or medical tourism, though both are worthy of further research. In this article, two concepts in the field of psychoanalysis are briefly introduced to pave the way for interdisciplinary scholars’ future research.The first concept is existentialist psychotherapy, which focuses on the existential and ultimate anxieties of human beings that stem from human “being”. This treatment is mainly based on intuition rather than experience. Humans› ultimate concerns are the conflicts caused by man›s confrontation with the realities of life. Even though such a confrontation is initially painful and scary, it is ultimately healing. These four basic concerns are «death, freedom, isolation, and meaninglessness.» What existential theorists agree on is that «now» is the most significant «time» in existential psychotherapy. In this approach, a person accomplishes inner and existential discovery and then reflects on his existential condition. This thinking is not limited to time and is about yourself. The past and memories of the individual are important as long as they make up his current being and affect how he deals with his fundamental anxieties. Existential psychotherapy is a type of psychodynamic therapy. In this paradigm, the visible behaviors of people are a function of internal processes and concealed events in their minds. The task of the existential therapist is to push aside daily worries person and make him/her think deeply about his/her four existential anxieties. The second concept that can be proposed in this field is obsessive-compulsive disorder (OCD). Obsession is an emotion or impulse that repeatedly, involuntarily, and unconsciously, and against a person›s will, enters his consciousness, and sometimes it is so debilitating that it prevents a person from doing daily tasks. Obsession is one of the most common disorders in the world. Almost one out of every fifty people suffers from this disorder at some point in their lives. This compulsion is always unpleasant and deprives the sufferer of the joy of life. Usually, very organized and perfectionist people are more susceptible to this disorder. It is interesting to note that the permanent treatment for this disorder is cognitive therapy. This means that the therapy requires the patient to change his intellectual structure, attitude, and interpretation of his life. Also, the increase of serotonin (happiness hormone) in the brain, the change of the person›s position, the change of space, and the conditions that make him do unpleasant forced work are among the boosters of this treatment path. The argument here is that «tourism» has a high capacity for treating fundamental anxiety and disorders such as obsession. Tourism is therapeutic in nature. As it is the epistemological system, it requires traveling to new places and encountering different cultures, histories, art, and customs. Tourism not only increases the knowledge and awareness of tourists but also develops their critical and creative thinking abilities. In today›s world, different types of tourism, from traveling to pristine landscapes to experiencing « slow tourism», being at the destination and embracing the unexpected without planning and perfectionism; giving more importance to quality than quantity; having a flexible schedule is something like an exploration; or «creative tourism,» which encourages interaction with living culture (and not visiting heritage) and promotes local people, from sellers to teachers, and tourists, from buyers to learners, inevitably take one out of his daily life and improve him. Inevitably, it changes his usual view of life and his perspective. It provides the conditions for experiencing an authentic life and living in the moment. Routine traps a person in regret for the past and fear of the future. Escaping from routine and breaking habits is what makes a person realize the time “now”. Tourism is an opportunity to enjoy special and exclusive experiences. Tourism is an opportunity to develop «self» and explore the culture, customs, attitude, and vision of «the other». Tourism is an opportunity to find and make meaning. Tourism is climbing Maslow›s pyramid and reaching the peak of self-actualization. Tourism is finding kindred; it is creativity, pleasure, edification, a way out of neglect, and philosophizing.Tourism puts one’s mind at rest by taking one away from the usual pressures of life; it broadens one’s perspective by familiarizing one with different environments and cultures. It reduces isolation and meaninglessness by providing the opportunity to get close to others with whom one does not know or have a relationship. It fosters personal development and growth through diverse experiences, which can be gained far from home and at the destination. It develops one’s talent and creativity through travel, and tolerance and acceptance through living with people from various cultures. It creates joy and happiness by immersing one’s body and soul in the host community, which can occur through attending traditional rites and harmonizing with the music, dance, and happiness of the people, experiencing various flavors, talking with fellow humans with different appearances and behaviors, and visiting the history of the past. Such a flow of life leaves no room for feelings of meaninglessness, isolation, fear of death, and constant obsessions.These cases demonstrate the high potential of tourism for existential therapy, healing various types of anxiety and obsession. However, establishing more specific causal correlations in “tourism therapy” requires a lot of interdisciplinary studies and research.